2018
DOI: 10.1038/s41589-018-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of silent biosynthetic gene clusters using transcription factor decoys

Abstract: Here we report a transcription factor decoy strategy for targeted activation of eight large silent polyketide synthase and non-ribosomal peptide synthetase gene clusters, ranging from 50 to 134 kilobases in multiple streptomycetes, and characterization of a novel oxazole family compound produced by a 98-kb biosynthetic gene cluster. Due to its simplicity and ease, this strategy can be readily scaled up for discovery of natural products in streptomycetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 23 publications
0
85
0
2
Order By: Relevance
“…The resulting mutants, IsgriM25 and IsgriM38, grown on mannitol soya flour solid medium showed no obvious phenotypical difference compared to the control strain sgriCK (wild type bearing the self-replicable plasmid pKC1139). However, switching to maltose-yeast extract-malt extract (MYM) liquid medium (38) appeared to be lethal for IsgriM25 ( Fig. 3 B and C)-a phenomenon that suggested that sgriM25 may be conditionally essential for the producer.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting mutants, IsgriM25 and IsgriM38, grown on mannitol soya flour solid medium showed no obvious phenotypical difference compared to the control strain sgriCK (wild type bearing the self-replicable plasmid pKC1139). However, switching to maltose-yeast extract-malt extract (MYM) liquid medium (38) appeared to be lethal for IsgriM25 ( Fig. 3 B and C)-a phenomenon that suggested that sgriM25 may be conditionally essential for the producer.…”
Section: Resultsmentioning
confidence: 99%
“…The bottleneck of transcriptional silence continues to drive innovation and a plethora of different approaches exist to activate silent pathways [199][200][201] . Advances in analytical techniques (mass spectrometry, NMR imaging and data analysis software) [202][203][204][205] allow us to better detect and characterize compounds produced in minute quantities, a major bottleneck in the field, lifting the veil on 'silent' NPs to further increase the number of unusual molecule leads, in addition to identifying critical pathway intermediates that may aid in deciphering cryptic pathways.…”
Section: Unlocking Nature's Diversitymentioning
confidence: 99%
“…However, the TFD strategy was used for the first time to activate the cryptic BGCs in Streptomycetes [63]. As it is difficult to exactly predict the regulatory DNA fragments in the BGCs, DNA fragments of approximately 100 base pairs were cloned to both the upstream and downstream of open reading frames (ORFs) in the target BGC.…”
Section: Transcription Factor Decoys Approachmentioning
confidence: 99%
“…This strategy is simpler than other strategies that use deletion or genome editing, such as the deletion of a negative regulator. However, the efficiency of this approach is not high at about 36-50% for the activation of silent BGCs [63]. Therefore, there is still room to improve this strategy by further engineering strategies.…”
Section: Transcription Factor Decoys Approachmentioning
confidence: 99%